How the communicative development inventories can contribute to clinical assessments of children with speech and language disorders - Eriksson, Mårten; Myrberg, Karin (Frontiers in Psychology, 2023)
The purpose of the present study was to investigate whether information from the Swedish version of the Communicative Development Inventories III (SCDI-III) is informative to the Speech and Language Pathologist (SLP) when examining children with suspected speech and language disorders at a SLP unit. Parents to 50 children (25 girls, 25 boys, age 30-80 months) that had been referred to the local SLP unit completed the SCDI-III. Nine children came from multilingual families and 41 children came from monolingual, Swedish speaking homes. The children were diagnosed as having developmental speech disorders (12) or developmental language disorders (33). Five children were not diagnosed with any disorder. The results showed that the referred children performed significantly lower on scales for word production, grammar, and metalinguistic awareness, compared to a subset from the norms with a similar age and gender composition. Most children fell below the 10 th percentile on word production and grammatical constructions. The intercorrelation between the three scales were in general substantial. Comparisons of children's performance on the vocabulary and grammar scales of SCDI-III, and the medical records revealed 18 cases of discordance that would have motivated further examination. The parents rated sometimes their child's vocabulary and grammar skills as higher and sometime as lower to the medical records.Limitations due to attrition and sample size were discussed. It was concluded that the SCDI-III can provide valuable information to the examination at the SLP clinic in addition to parent interviews, observations of children, and various tests, and that the potential for adapted versions would be particularly high for examinations of multilingual children.